Protection Ability Comparison of Several Mosquito Repellent Lotion Incorporated with Essential Oils of Mosquito Repellent Plants - Utomo, Pramono Putro; Supriyatna, Nana (Biopropal Industri, 2014)
Most mosquito repellent lotions available on the market today contain the active ingredient diethyltoluamide (DEET) which is very harmful to the skin. Natural mosquito repellent research using various essential oils (geranium oil, lemon oil, citronella oil and lavender oil) as the active ingredient and the addition of aloe vera gel as a moisturizer has been done on a laboratory scale. The purpose of this study was to compare the protection ability of the mosquito repellent plants in Indonesia. The results showed that geranium oil, lemongrass oil, lavender oil and lemon oil could act as mosquito repellent. Best lotion formula all containing 15% essential oils have the effectiveness above 50% until the sixth hour were geranium oil, citronella oil and lavender oil while lemon oil only giving effectiveness above 50% until the second hour.